Detecting Keratoconus in Primary Healthcare: What general practitioners could do? Poster Presentation - Case Report - General practitioner - Akbar, Muhammad Khalil; Samira, Cut Putri (Majalah Oftalmologi Indonesia, 2023)
Introduction : Keratoconus (KC) is a rare eye disorder that causes corneal thinning and visual disturbances. KC prevalence in the pediatric population is 0.16%. Children with keratoconus experience faster disease progression and significant visual impairment at diagnosis, impacting their quality of life. This case report aims to raise awareness and provide knowledge regarding KC for general practitioners. Case Illustration : A 14-year-old male visited a primary healthcare facility complaining of difficulty seeing words on the classroom board for the past year. His best-corrected visual acuity was 6/15 (S-10.25 C-5.25x30) OD and 6/60 (S-25.00 C-2.75x150) OS. Upon examination, it was observed that the left cornea was more protruding than the right, with a positive Rizzuti and Munson sign. Based on the findings, the patient was suspected of having keratoconus with amblyopia and was referred to an ophthalmologist for further examination and management. Discussion : Keratoconus is severe and burdensome to society, impacting children's education and quality of life. Early detection and intervention are crucial to prevent worsening. KC can be detected in primary healthcare by observing external signs such as Rizzuti and Munson. KC can lead to severe vision problems and even amblyopia if left untreated. Treating pediatric KC involves improving vision using contact lenses. In cases where contact lenses cannot be used, keratoplasty may be necessary. Conclusion : Primary healthcare providers can identify and assess keratoconus in patients and make referrals to ophthalmologists for treatment to minimize the impact on vision and stop its progression.